IMPLEMENTASI ASAS-ASAS UMUM PEMERINTAHAN YANG BAIK TERHADAP KEPUTUSAN BERSIFAT BESCHIKKING DALAM TATA USAHA TENTARA NASIONAL INDONESIA - Djodi Suranto (Jurnal Hukum dan Peradilan, 2017)
Implementation of good governance general establishment and application in the formation of good governance implementation in Indonesian National Army (TNI) Administration in the Central Office and Base Office (Mabes TNI), and also its roles in equipping the weakness, ambiguities and lack of ordinance as a law finding. Results of this study find and reveal the implementation of several principles, having formal in character, they are: prudent preparation principle, motivation and prohibition in procedural abuse, and matrial character are: law certainty, trust and expectation, prohibition on authority abuse and equality principles. The principles are applied due to its formation is in accordance with prevailed, developed and grown custom law in governance implementation practice, and also because it is according to the higher law norms and also the existing relationship between factual conditions with the incurred consequences. Thereinafter, the principles have very important roles in fulfilling the weakness and ambiguities and also the lackness of ordinance as law finding for the formation of good governance implementation in Indonesian National Army Administration. Keyword: good governance general establishment and application, beschikking, Indonesian National Army